Malnutrición y su relación con la enfermedad periodontal - Silva Acosta, Selena Fernanda (2022)
This research aimed to determine the association between malnutrition and periodontal disease, establishing the relationship between the pathophysiology of periodontal disease and nutritional deficit using a literature review through publications corresponding to the last ten years. The articles obtained were from scientific databases such as PubMed, Google Scholar, Elsevier. A total of 112 articles were obtained by evaluating their impact through the Scimago Journal Ranking and validation according to the average citation count subject to inclusion and exclusion criteria, obtaining 74 articles. It was found that obesity could exacerbate periodontal tissue destruction and disease severity due to an induced pro-oxidant state in periodontal tissue. Overweight patients showed a poor attitude toward oral hygiene, changes in immune response, increased psychosocial stress, and excess caloric intake in a poor dietary habit. Several hypotheses have been proposed for biological interactions between obesity and periodontal diseases, such as changes in pro-inflammatory and immune responses, glucose intolerance, alterations in lipid profiles, alterations in host immunity, increased macrophage activation, microvascular alterations, physiological responses to psychosocial stress, and secretion of pro- inflammatory substances from adipose tissue, including TNF-α, IL-6, and C-reactive protein. It is essential to prevent obesity and promote oral health by modifying the consistency of the diet, decreasing the consumption of sugary and non-nutritious foods.